Using Graphs in Sexual Violence Risk Communication: Benefits May Depend on the Risk Metric. (September 2021) - Hilton, N. Zoe; Helmus, L. Maaike
Actuarial scales provide a relatively objective and reliable assessment of individuals' risk of recidivism. Recent research has explored how graphs can improve quantitative risk communication. We tested whether graphs can improve understanding and perception of sexual violence risk when matched with risk metric. Participants ( N = 676) were recruited from Amazon's MTurk platform and read a brief description of a man convicted of a sexual offense, including results of a fictional sexual recidivism risk scale. In Study 1, absolute risk of recidivism enabled participants to distinguish between individuals with relatively high and low risk of sexual recidivism. In Study 2, this distinction was enhanced by adding a graph, especially when percentiles were communicated. Risk ratios increased perceived risk. Objective numeracy increased understanding and reduced perceived risk. We recommend that risk communication assumes limited statistical numeracy, and further research with practitioners to test the effect of graphs and risk metrics on forensic/judicial decisions.